Tri Hita Karana Implementation in Accommodation Management (The Case of Traditional Balinese Homestays in Ubud) - Solihin; Ida Ayu Ketut Sumawidari (International Journal of Glocal Tourism, 2021)
Abstract : Purpose: This research paper discusses the implementation of Tri Hita Karana in the development and management of traditional Balinese homestays in Ubud, Bali, Indonesia. Research methods: The qualitative research which data are obtained through observation, literature study, and in-depth interviews with several informants, namely observers of Balinese cultural tourism and owners and managers of homestays in Ubud. Findings: Traditional Balinese homestays in Ubud are buildings where local residents live in the form of umah "pondok" or new buildings that are prepared for tourists. They are built with a traditional Balinese architectural model that refers to the Tri Mandala and Tri Hita Karana philosophy that reflect the harmonious relationship between humans and God (parahyangan), humans and each other (pawongan), and humans and their environment (palemahan). Implications: The existence of traditional homestay in Ubud that are able to support the sustainability of tourism development in Bali needs to be maintained.